A Multidimensional Model for Mapping the Digital Divide in Indonesia’s Underdeveloped, Frontier, and Outermost (3T) Regions through a Systematic Literature Review Approach - Syahrul Hidayanto; Billy Sarwono; Ilya R. Sunarwinadi; Irwansyah (Fakultas Usluhuddin dan Dakwah UIN Syekh Wasil Kediri, 2026)
This study aims to map the digital divide in Indonesia's Underdeveloped, Frontier, and Outermost (3T) regions through a multidimensional approach using the Systematic Literature Review (SLR) method. Given the increasingly complex digital divide, which no longer centers on access alone, this study examines four main dimensions: access, usage, digital capability, and digital outcomes. Furthermore, this study examines the social, psychological, economic, and institutional determinants that contribute to variations in disparities between community groups. The researchers employed the SLR method following the PRISMA 2020 protocol and analyzed 29 articles from Q1 Scopus-indexed journals published between 2019 and 2025. The data analysis indicates that limited digital infrastructure, low digital literacy, inadequate socio-institutional support, and psychosocial barriers, such as technology anxiety, collectively exacerbate the digital divide, particularly for vulnerable groups, including women, older adults, teachers, and low-income communities. Furthermore, the findings also indicate that infrastructure alone is insufficient to address the digital divide without strong literacy interventions, technological trust, and community support. Furthermore, the digital divide significantly affects access to essential public services, including education, digital health, and economic opportunities. Ultimately, this study offers a multidimensional model that integrates technical, social, psychological, and institutional factors to elucidate the structure of the digital divide in Indonesia's 3T regions, providing a conceptual foundation for formulating more targeted digital inclusion policies.